Bacterial Pathogens Detected Among Domestic Animals In Ludhiana And Their Resistance To Various Antibiotics. - Kaur, P.; Saxena, H.M.; Chandra, M.; Kaur, G.; Deepti; Arora, A.K.; Rai, T.S.; Dwivedi , P.N.; Sharma , N.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
A total of 611 clinical samples from various species of domestic animals were analyzed for the presence of pathogenic bacteria and their sensitivity to common antibiotics. Staphylococci and E. coli were found to be the most common pathogens in these samples. E. coli from most of the species were resistant to Penicillin and Enrofloxacin while Staphylococci from cows were found to be resistant to Ampicillin.
Keywords: Staphylococci; E. coli; Bacillus; Antibiotics; Resistance; Sensitivity